Revolt and Resistance in the Anglo-Irish War: Jesuit Influences and Spanish Connections in Late Elizabethan Ireland - Jane Yeang Chui Wong (Caliban: French Journal of English Studies, 2022)
Studies that examine the last decade of Elizabethan Ireland have generally been preoccupied with discussions about the Nine Years War (1596-1603) and the struggle for dominance between the Irish confederacy and the English government. Cornered into taking sides between faith and state, English Catholics in Ireland became subjects of suspicion in the eyes of Elizabethan authorities. In Spain, Philip III’s lukewarm responses to the confederacy’s appeals were associated with the political ramifications that could potentially worsen Anglo-Spanish relations. This essay focuses on the diplomatic dimensions of the Anglo-Irish conflict against the backdrop of Anglo-Spanish tensions and re-evaluates the origins of Hiberno-Spanish relations in Elizabethan Ireland. Within this context, my analysis of the exchanges between the Spanish council and the Irish confederacy analyses the ways in which diplomatic relations among England, Ireland, and Spain shaped a narrative that extirpates the Irish confederates’ “faith and fatherland” ideology, paving a way to a new order that privileged practical diplomatic benefits over religious imperatives.